2002
DOI: 10.1021/bi012153k
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Calcium-Binding Studies of a Recoverin Mutant (E85Q) in an Allosteric Intermediate State

Abstract: Recoverin, a member of the EF-hand superfamily, serves as a calcium sensor in retinal rod cells. A myristoyl or related fatty acyl group covalently attached to the N-terminus of recoverin facilitates the binding of recoverin to retinal disk membranes by a mechanism known as the Ca2+-myristoyl switch. Previous structural studies revealed that the myristoyl group of recoverin is sequestered inside the protein core in the absence of calcium. The cooperative binding of two calcium ions to the second and third EF-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
113
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 41 publications
7
113
0
Order By: Relevance
“…2 A). The exposed hydrophobic residues in this region are conserved and correspond to residues of recoverin that interact with the myristoyl group in the Ca 2ϩ -free state (69,95,96). Upon Ca 2ϩ binding, these exposed residues in the hydrophobic patch have been implicated in target recognition from mutagenesis studies (97-100), and these residues form intermolecular contacts with target proteins as observed in the recent crystal structure of KChIP1 (101).…”
Section: Structure and Target Recognition Of Ncs And S100 Proteinsmentioning
confidence: 94%
“…2 A). The exposed hydrophobic residues in this region are conserved and correspond to residues of recoverin that interact with the myristoyl group in the Ca 2ϩ -free state (69,95,96). Upon Ca 2ϩ binding, these exposed residues in the hydrophobic patch have been implicated in target recognition from mutagenesis studies (97-100), and these residues form intermolecular contacts with target proteins as observed in the recent crystal structure of KChIP1 (101).…”
Section: Structure and Target Recognition Of Ncs And S100 Proteinsmentioning
confidence: 94%
“…The structure of recoverin has been extensively studied by X-ray crystallography and NMR studies to interrogate its structure in its Ca 2þ -bound and -free forms (Flaherty et al 1993;Ames et al 1995;Tanaka et al 1995;Ames et al 1997;Ames et al 2002;Weiergraber et al 2003). Recoverin is composed of two distinct domains connected through a bent linker and forms a compact structure in the absence of Ca 2þ .…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 99%
“…Consequently, the myristoyl group is still sequestered within a hydrophobic cavity and only partially unclamped. Biochemical studies on the myristoylated E85Q mutant confirmed that it can only bind one Ca 2ϩ at saturating concentration (21,22). Intriguingly, a fraction of myristoylated E85Q recoverin binds to membranes already at low free Ca 2ϩ (2-9 M), indicating that the presence of lipid bilayers may shift the conformational equilibrium toward a form of the E85Q mutant in which the myristoyl chain is exposed (22).…”
mentioning
confidence: 99%
“…An intermediate state with Ca 2ϩ bound solely to EF-3 can be prepared using myristoylated recoverin harboring the mutation E85Q, which virtually abolishes Ca 2ϩ binding to EF-hand 2. Recently the three-dimensional structure of the myristoylated E85Q mutant was determined by NMR spectroscopy (21). It was shown to exhibit a hybrid fold with the N-and C-terminal domains resembling the corresponding portions of Ca 2ϩ -free and Ca 2ϩ -bound myristoylated wild-type recoverin, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation